Vimentin as a contributing factor in SARS-CoV-2-induced orchitis on postmortem testicular autopsy of COVID-19 cases: A case-control study - Soheila Akaberi-Nasrabadi; Azam Sabbaghi; Behzad M. Toosi; Parsa Ghorbanifaraz; Gholam-Reza Mahmoudiasl; Abbas Aliaghaei; Hajarsadat Faghihi Hosseinabadi; Shahrokh Paktinat; Mohammad-Amin Abdollahifar (International Journal of Reproductive BioMedicine)
Background: Coronavirus disease 2019 (COVID-19) was identified in China in late December 2019 and led to a pandemic that resulted in millions of confirmed cases and deaths. The causative agent, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), uses distinct receptors and co-receptors to enter host cells. Vimentin has emerged as a potential co-receptor for SARS-CoV-2 due to the high level of vimentin expression in testis tissue.